The Existence of Veldbox as a Colonial Historical Heritage and Its Relevance to Social Studies Learning in Elementary School - Hamna; Muh. Khaerul Ummah BK; Intan Nuraini; Evi Afrianti (Madako Elementary School, 2026)
Colonial historical heritage in various regions of Indonesia continues to face challenges in preservation and educational utilization. One example is the veldboxes in Tolitoli Regency, which remain relatively unfamiliar to local communities and have not been optimally integrated into educational practices. As a result, students have limited understanding of their local history. This study aims to examine the existence of veldboxes as Dutch colonial heritage in Tolitoli Regency and explore their relevance to elementary Social Studies education. A qualitative approach was employed using Archaeological Object Study and Field Research methods at seven Dutch colonial veldbox sites. Data were collected through field observations, documentation, and interviews with local historians, nearby residents, teachers, and the principal. The findings indicate that the veldboxes were constructed around the 1940s as defensive bunkers and coastal observation posts. Their conditions vary from relatively intact to severely damaged, with only two sites officially designated as cultural heritage assets. The study also found that veldbox history has not yet been integrated into Social Studies instruction at SDN 1 Nalu. Nevertheless, these structures have considerable potential as contextual local-history learning resources through field visits, visual media, and instructional modules, thereby enhancing students’ historical understanding and cultural awareness.